POTENCY AND DEVELOPMENT OF ECOTOURISM OF BUTTERFLY PARK IN SESANDAN VILLAGE, TABANAN REGENCY - I Putu Budiarta; I Ketut Ardiasa; I Wayan Nurjaya; I Nyoman Kanca (Soshum: Jurnal Sosial dan Humaniora, 2017)
Purpose of this research is to identify the potencies and development of Butterfly Park in Sesandan Village, Tabanan Regency. Data of this research were collected through observation, in depth interview, and questionnaires. The findings showed that the butterfly park in Sesandan Village has 4 (four) tourism components namely attraction, accessibility, amenity, and ancillary (4 A). Those components should be developed so that the number of visitors to the village could increase. The development includes some strategies such as Strength-Opportunities Strategy which include development of small scale tourism, alternative tourism and sustainable tourism. Weakness-Opportunities Strategies which include the development of human resources in Sesandan Village on knowledge and skill in tourism. Strength-Threats Strategies, which include keeping and increasing the security of Sesandan Village and by doing benchmarking to the more-developed destination. Weakness Threats Strategies which is done by preserving the ecosystem of the butterfly to keep the balance of the nature and to enlarge the area of the conservation so that it becomes more attractive to be visited.